Kardas-Nelson, Mara. We Are Not Able to Live in the Sky: The Seductive Promise of Microfinance - Meager, R. (Journal of Economic Literature, 2025)
R. Meager of University of New South Wales reviews “We Are Not Able to Live in the Sky: The Seductive Promise of Microfinance” by Mara Kardas-Nelson. The Econlit abstract of this book begins: “Explores how microfinance, the practice of lending small amounts of money directly to people facing poverty, has impacted the lives of borrowers, highlighting the experiences of women in Sierra Leone who took out microfinance loans.”